Institutional investors in Germany: Insurance companies and investment funds - Raimond H. Maurer (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
This chapter focuses on institutional investors in the German financial markets. Institutional investors are specialized financial intermediaries who collect and manage funds on behalf of small investors toward specific objectives in terms of risk, return and maturity. The major types of institutional investors in Germany are insurance companies and investment funds. We will examine the nature of their businesses, their size and role in the financial sector, the size and the composition of the assets under their management, aspects of financ ial regulation, and features of their asset-liability-management.
urn:nbn:de:hebis:30-18094
Keywords: G22; G23; G28; 330; Institutional Investors; Insurance Companies; Investment Funds; Regulation; Pension; Institutioneller Anleger; Versicherung; Investmentfonds; Deutschland